Characteristics Of Two Original Facades (Gable and Gunungan) Of Malabero Chinese Shop House In Bengkulu City - Anggi Yudha Pratama; Juwito, Rizqiyah Safitri; Pratimi, Mariska; Sari, Renitha (International Journal of Applied Research and Sustainable Sciences, 2024)
Building facades convey a period of culture at the time the building was built, as well as providing the identity of a cultural group or community. Building facades and anthropology became the impetus to find out the original characteristics of the two main facades in the row of Malabero Chinese shophouses on Jalan D. I. Panjaitan Bengkulu City. This research uses the field observation method to obtain data through photographs as well as information from the surrounding community, historians, and cultural experts in Bengkulu and Malabero Chinese Village, to get a link to the facade pattern with an emphasis on building facade elements (roof, walls and building openings) through variables of Chinese shophouse facade characteristics and shop house facade indicators. Malabero Bengkulu's Chinese shophouses are grouped within the Chinese settlement (Chinese Kamp) in front of Fort Marlborough, initially having two characteristics of Chinese shophouse building styles based on their facades. The alteration of the south side of the Malabero Chinese shophouses eliminated many of the original characteristics of the original facade of the Malabero Bengkulu Chinese shophouses (gable roof). As a result, many new characteristics of the shophouse facade elements have been replaced. The shape of the roof (gunungan), the removal of the balcony, and the shape of the building openings became the characteristics of the facade face of the south side Malabero Chinese shop house (gunungan roof). This change in the facade is in anticipation of the load being responsive to earthquakes.